Addressing smoking in sheltered homelessness with intensive smoking treatment (ASSIST project): A pilot feasibility study of varenicline, combination nicotine replacement therapy and motivational interviewing. (January 2022) - Skelton, Eliza; Lum, Alistair; Cooper, Lucy E.; Barnett, Emma; Smith, Julie; Everson, Arlene; Machart, Jane; Baker, Amanda L.; Halpin, Sean; Nielssen, Olav; Clapham, Matthew; Bonevski, Billie
Highlights: Varenicline, NRT and MI is a feasible, safe, and effective. Participants held concerns regarding varenicline safety and efficacy. Counselling and NRT were viewed as acceptable strategies. Education regarding varenicline safety is warranted. Abstract: Background: This pilot study aimed to test the feasibility of providing varenicline in combination with nicotine replacement therapy (NRT) and motivational interviewing (MI) to adult male smokers attending a clinic in a hostel for homeless people. Methods: A single group pre- and post-treatment (12 weeks following intervention commencement) design with embedded process evaluation (at weekly counselling and fortnightly safety check-ins). Participants were 20 male smokers attending a health clinic within a homelessness service in Sydney, Australia, between December 2019 and March 2020. Participants set a target quit date 7-days post intervention commencement. Adverse events, self-reported abstinence, cigarettes per day, treatment adherence and acceptability of the study interventions were assessed 12 weeks post intervention commencement. Abstinence was biochemically verified. Results are complete cases. Results: Retention was 65% at 12-weeks post-intervention commencement (n = 13). No related adverse events were reported. Three participants (15%) reported continuous abstinence. Two participants self-reported 30-day point prevalence abstinence (10%), confirmed by CO level. Participants who did not quit smoking (n = 10), reported a significant reduction in the number of cigarettes smoked per day (19.4 vs 4.7, p < .01). Cravings, withdrawal symptoms, and psychological distress significantly decreased from baseline to 12-week follow-up (all < 0.01). Adherence to the pharmacological interventions was good, most used combination NRT and varenicline. Adherence to the counselling sessions was low, attending three of 12 sessions. Both NRT and MI were rated as highly acceptable. Some participants expressed concerns about the safety of varenicline. Conclusions: The intervention was feasible and acceptable and associated with short-term smoking cessation and significant reductions in the number of cigarettes smoked-per-day.